2017
DOI: 10.15256/joc.2017.7.107
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Heart Disease Risk in Patients with Schizophrenia: A Lebanese Cross-Sectional Study

Abstract: Background:Coronary heart disease (CHD) is a leading cause of premature death in patients with schizophrenia. CHD risk in Lebanese patients with schizophrenia remains unknown.Objectives:To (i) evaluate CHD risk of patients with schizophrenia in Lebanon; and (ii) detect the modifiable and non-modifiable factors affecting this risk.Methods:Cross-sectional study of 329 patients with schizophrenia aged 20–75 years. Ten-year hard CHD risk was calculated using the Framingham risk score. A logistic regression was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…These populations are at increased risk of infectious disease outbreaks as they reside in close overcrowded environment and interact closely and frequently with nursing staff, and use shared spaces, such as bathrooms and dining room [6]. In addition, psychiatric patients has high rates of physical health comorbidities, such as obesity, hypertension, and metabolic syndrome, as well as high rates of neurocognitive impairment [7][8][9][10]. They are more likely than the general population to become infected with COVID-19, and they are more than twice as likely to develop a severe outcome of COVID-19 infection [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These populations are at increased risk of infectious disease outbreaks as they reside in close overcrowded environment and interact closely and frequently with nursing staff, and use shared spaces, such as bathrooms and dining room [6]. In addition, psychiatric patients has high rates of physical health comorbidities, such as obesity, hypertension, and metabolic syndrome, as well as high rates of neurocognitive impairment [7][8][9][10]. They are more likely than the general population to become infected with COVID-19, and they are more than twice as likely to develop a severe outcome of COVID-19 infection [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors among psychiatric patients for severe infection are highly prevalent, such as increased rates of obesity, cardiovascular disease and chronic obstructive pulmonary disease [8,[13][14][15]. In addition, gender is a risk factor for increased severity and death in individuals with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Mania, the most typical phase of bipolar disorder type I (BD‐I) also known as disabling disorder, is characterized by functional impairment leading to high rates of morbidity and mortality, and an increased risk of suicide, contributing to reduced life expectancy, and lower quality of life . Several studies had showed an excess mortality in people with severe mental illness (SMI), two to three times higher than that of the general population . About 60% of this excess mortality is due to one or more physical illnesses that are frequent in manic patients; one physical comorbidity is seen in over 80% of patients, while 19% to 23% have 2, and 35% to 40% suffer from 3 or more .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with serious mental illness, including schizophrenia, have metabolic abnormalities and cardiovascular diseases [20][21][22] being largely attributed to increased mortality rates, more than the factors directly associated with the psychiatric illness. In addition, obesity is a major public health problem and negatively affects the life of affected individuals.…”
mentioning
confidence: 99%